Desflurane anaesthesia in myotonic dystrophy - Gandhi, Ranju (Medknow Publications, 2011)
Myotonic dystrophy (MD) is a rare genetic disorder with multisystem involvement characterised by myotonia and progressive muscle weakness and wasting. These patients pose significant challenges to the anaesthesiologist in view of the muscular and extramuscular involvement and sensitivity to anaesthetic drugs. The literature is replete with reports of postanaesthetic respiratory and cardiovascular complications in these patients. But an ideal anaesthetic technique in MD patients remains to be determined. Rapid recovery is desirable to reduce postoperative respiratory complications. Though there are a few case reports of maintenance of anaesthesia with isoflurane and sevoflurane, there are scanty reports of use of desflurane in these patients. We present successful management of a patient with MD for laparoscopic cholecystectomy using a carefully titrated desflurane-based anaesthesia and discuss the perioperative considerations.